Statistical Determination of Factors for Best Marketing Practices of Urban and Reclaimed Wood as Raw Material - Sánchez-Chinchilla, Alejandro (2020)
This research is about statistical determination of factors indicated as benefits and barriers, regarding the urban and reclaimed wood in United States market. Through literature review was identified 14 and 8 variables cataloged as benefits and barriers respectively, to conform an initial model, which was consulted to 390 companies of this market for the measurement of the importance level of each variable based on company’s experience. This was made through a survey as research tool, validated by methodologic triangulation (surveys experts, academic area experts and industry experts). The initial model was reduced into a management model with 6 and 4 factors for benefits and barriers respectively, containing the correlated variables. For current situation diagnosis was confirmed that this market is relative new, on its majority is the reclaimed wood more used as raw material than urban wood, and that there is a low percentage of benefits variables on company’s advertising. Solutions to proposed problems are a management model and a propose for best marketing practices, which can increase incomes that could generate 60% of net profit. Conclusions are that is possible condense the variables found on literature into a simpler model, which can work as a validated source of information to better marketing strategies, and the recognition of the barriers for this raw material utilization